Problem pojednania polsko-niemieckiego w działalności społeczno-politycznej premiera Brandenburgii Manfreda Stolpe = The problem of Polish-German reconciliation in the social and political activity of Manfred Stolpe, the prime minister of Branderburg - Hładkiewicz, Wiesław; Ilciów, Adam (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The Prime Minister of Brandenburg, Manfred Stolpe, undoubtedly contributed to the development and consolidation of socio-political relations between Poland and Germany. His activity in the area of the development of cooperation between the regions on both sides of the border needs to be appreciated, too. However, he was suspected of collaborating with Stasi, which puts him in a bad light. This paper tries to clarify these doubts.
Keywords: stosunki polsko-niemieckie; pogranicze polsko-niemieckie; pojednanie; Stolpe, Manfred (polityk niemiecki; 1936-2019)